1991
DOI: 10.1002/macp.1991.021921021
|View full text |Cite
|
Sign up to set email alerts
|

Properties of poly[N‐2‐(methyacryloyloxy)ethyl‐N,N‐dimethyl‐N‐3‐sulfopropylammonium betaine] in dilute solution

Abstract: Poly[N-2-(methacryloyloxy)ethyl-N,N-dimethyl-N-3-sulfopropy~ammonium betaine] (1)which is an interesting polyzwitterion polymer by virtue of its "antipolyelectrolyte solution behaviour" has been prepared by free-radical initiated polymerization in aqueous solution.Isothermal fractionation was conducted at 294 K employing formamide as solvent and acetone as precipitant. -Welve fractions covering a wide range of weight-average molecular weight (21 5 OOO 5 M , 5 2070000) were used to characterise the polymer by l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 17 publications
2
53
1
Order By: Relevance
“…Besides water and aqueous salt solution, polysulfobetaines are generally soluble only in organic solvents such as 2,2,2‐trifluoroethanol TFE, trifluoroacetic acid (TFA), and in some instances formamide. Given that TFE has previously been shown to be a thermodynamically better solvent than salt solution,30 and that Lowe et al5 have also demonstrated that it is a suitable solvent for the molecular dissolution of low molecular weight DMAEMA‐methyl methacrylate block copolymers, we opted to use this as the organic cosolvent. Given the need for dissolution in TSB, clearly not all the copolymers reported in Table I were anticipated to be viable test materials given the hydrophilic and hydrophobic compositions of the materials.…”
Section: Resultsmentioning
confidence: 99%
“…Besides water and aqueous salt solution, polysulfobetaines are generally soluble only in organic solvents such as 2,2,2‐trifluoroethanol TFE, trifluoroacetic acid (TFA), and in some instances formamide. Given that TFE has previously been shown to be a thermodynamically better solvent than salt solution,30 and that Lowe et al5 have also demonstrated that it is a suitable solvent for the molecular dissolution of low molecular weight DMAEMA‐methyl methacrylate block copolymers, we opted to use this as the organic cosolvent. Given the need for dissolution in TSB, clearly not all the copolymers reported in Table I were anticipated to be viable test materials given the hydrophilic and hydrophobic compositions of the materials.…”
Section: Resultsmentioning
confidence: 99%
“…bases (1 M Na 2 CO 3 , NaOH, KOH and NH 4 OH) and aq. salts (1 M KSCN, KCl, KBr, NH 4 Cl, KI and (NH 4 ) 2 S 2 O 8 ), processes (a) and (b) occurred at pH A 9 (i. e., NaOH, KOH, NH 4 OH and Na 2 CO 3 ). In contrast, neither (a) nor (b) took place in acidic and neutral media.…”
Section: B -Secondary Observationsmentioning
confidence: 99%
“…Similarly, the total swellability of a zwitterionic xerogel in aqueous salt is greater than that in water alone 2,[5][6][7] . Several studies have already been made on solutions and hydrogels of a common synthetic zwitterionic polymer, poly[N,N-dimethyl-N-methacryloyloxyethyl-N-(3-sulfopropyl)ammonium-betaine](PSPE) 3,4,6) .…”
Section: Introductionmentioning
confidence: 99%
“…7,8 These polymers mostly comprise polyzwitterions, in particular of the class of polysulfobetaines. [16][17][18] Although their thermo-responsiveness has been explored occasionally, actually quite some time ago, [19][20][21][22][23] this feature was considered rather a nuisance to their use (e.g. for producing biocompatible or low-fouling materials).…”
Section: Introductionmentioning
confidence: 99%
“…The strong dependence of the cloud points of P-1 on the concentration and on the type of added inorganic salts, in particular on the anion type in close correlation to the Hofmeister series, is well established. [20][21][22][23]43,57,[77][78][79][80][81][82] Therefore, the strong effects of the added salts and their relative impacts, observed for structurally closely related polymers P-2-P-8 are not surprising. Still, the widespread perception that the interaction of salts with polysulfobetaines can be treated as a general saltingin effect is not adequate, as evident from the evolution of the cloud points as a function of salt concentration.…”
mentioning
confidence: 99%